PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS MODEL SEARCH, SOLVE, CREATE, AND SHARE (SSCS) TERHADAP PEMAHAMAN KONSEP SISWA PADA MATERI MOMENTUM DAN IMPLUS - Nova, Alfiatin; Nor, M; Nasir, Muhammad (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2023)
This study aims to design learning tools based on the Search, Solve, Create and Share (SSCS) model on momentum and implus material for class X SMA and produce learning tools based on the Search, Solve, Create and Share (SSCS) model which are valid on momentum and impulse material. class X high school. This research was conducted at the Physics Education Laboratory, FKIP, University of Riau. The subject of this study was a Search, Solve, Create and Share (SSCS) based physics learning tool which was developed including the Learning Implementation Plan (RPP), Student Worksheets (LKPD), and learning achievement tests on momentum and impulse materials for class X SMA. In addition, the test subjects involved in this development research consisted of material experts, namely validators or teams/experts or physics education lecturers who validated SSCS-based science learning tools. The development model used in this study is Research and Development (R&D), with a 4D model. Based on the results of the research data it was concluded that the learning device using the SSCS model for the material on momentum and impulse for class X SMA was declared valid and suitable for use as a learning tool that helps teachers and students understand the material on momentum and impulse and can be used as teaching material in the learning process at school.